X-Efficiency and Scale Efficiency of Middle East Banks - Pillai, Pravin.R. (2013)
This paper surveys efficiency of banks specially operating in the Middle-East by applying frontier estimation technique. A 15 years period has been considered for the study of bank performance commencing from 1998 and going up to 2012. The primary goals of this study are to explore the dynamics of banking industry in the Middle-East and identify the key trends dominating the industry. A thorough literature review is conducted to understand the concept of efficiency by using STATA and exploring empirical evidence. Stochastic frontier approach is used to measure the cost efficiency of these banking operations and utilising Bankscope to derive the data from the banks operating in Middle-East. The findings and recommendation strategies shall help all banks in enhancing their x-efficiency and scale of such. The banking sectors where further research is needed are also outlined.